2019
DOI: 10.15171/ijhpm.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Regular Antenatal Care Visits Predict Good Knowledge Among Post-natal Mothers Regarding Entitlements of Health Programs in Western India

Abstract: Janani-Shishu Suraksha Karyakram (JSSK) and Janani Suraksha Yojana (JSY) were launched with the objective of increasing institutional deliveries. But, its knowledge among the post-natal mothers is not known. This research evaluated the knowledge of two national health programs among post-natal mothers and found out the predictors of good knowledge about the entitlements of these programs. A cross-sectional study was conducted on a sample of consecutively recruited 339 post-natal mothers who had delivered in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[19] Also, a study conducted by Rupani et al in Gujarat showed that 24% of mothers were aware of JSSK. [20] Around 93% of beneficiaries stayed for less than 48 hours, indicating poor health-seeking behavior of the community and implementation issues from the health facilities. Further, discharge within 48 hours could be attributed to demand and supply issues.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Also, a study conducted by Rupani et al in Gujarat showed that 24% of mothers were aware of JSSK. [20] Around 93% of beneficiaries stayed for less than 48 hours, indicating poor health-seeking behavior of the community and implementation issues from the health facilities. Further, discharge within 48 hours could be attributed to demand and supply issues.…”
Section: Discussionmentioning
confidence: 99%
“…The mothers had to pay an extra amount ranging from INR 12 to 700 for their foods. Rupani et al (2019) carried out a cross-sectional descriptive study in Sir Takhtsinhji hospital of Bhavnagar in Gujarat and found that 99.7% of the mothers were aware of the JSSK free diets provided during the stay, out of which 96.0% of mothers reported that they were offered free foods, whereas 16.0% of the mothers opted for homemade foods during their stay. To date, there are no studies reporting on the nutrient content analysis of the foods served through the JSSK programme.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that regular antennal check-ups helps in imparting good knowledge on the entitlements of health programs. [ 24 ] Angadi et al . also reported from south Indian settings that nuclear families, and low education of the beneficiaries or their husbands are associated with incurring high OOPE.…”
Section: Discussionmentioning
confidence: 99%